Edukasi Manajemen Menstruasi Sehat pada Santriwati di Pondok Pesantren Kabupaten Kediri - Byba Melda Suhita; Reni Yuli Astutik; Siti Komariyah; Shanty Natalia; Agustin Widowati (JCS, 2025)
Menstrual hygiene management (MHM) is essential for maintaining adolescent girls’ reproductive health, especially for students in Islamic boarding schools (pesantren) where access to information and sanitation facilities is limited. Proper education is crucial to reduce stigma, misconceptions, and improper hygiene practices during menstruation. This community service activity used a participatory educational approach through preparation, material development, implementation, and evaluation stages. The program targeted 38 female students aged 12–18 in a pesantren in Kediri Regency. Evaluation was conducted using pre-test and post-test with paired sample t-test analysis. Evaluation results showed a significant increase in knowledge scores from a mean of 91.68 to 95.13 (p < 0.001), despite initially high baseline scores. These findings indicate that a contextual educational approach effectively strengthens adolescents’ understanding of MHM. The improvement in knowledge was supported by relevant content and interactive delivery methods. Education based on cultural and religious values successfully reduced stigma and promoted healthy menstrual management behavior. MHM education programs in pesantren settings are proven effective in enhancing girls’ understanding. Similar initiatives should be scaled up and integrated into adolescent health education curricula. Keywords: menstrual hygiene management, health education, female students, Islamic boarding school, adolescent girls.